Regulation of the emotional states of boxing referees: a general reflection(Review) (Revista científica Olimpia, 2020)
The psychological preparation of the judges and referees plays an essential role in achieving the objectives during the competitions. The excessive nervousness in the performance and decision of the referees and judges in the fighting, cause insecurity and disgust in some of them; lacking alternatives in the regulation of emotional states, which does not favor adequate attention in the fighting. Hence, it was proposed as a scientific problem: what are the theoretical foundations that sustains the emotional states of boxing referees in the regulation of fear of failure during combat? Therefore, the objective of the research is framed in delimit the theoretical foundations that underpin the emotional states of boxing referees in the regulation of fear of failure during combat. The theoretical-methodological systematization reflected limitations in the approach to emotional states in boxing referees. The importance of this study lies in the theoretical assessment that is constituted in emotional states in boxing referees for the design of new psychological interventions.
Keywords: referee; boxing; emotional states; fear